Prevalence of integrase strand transfer inhibitor resistance mutations in antiretroviral-naive HIV-1-infected individuals in Cameroon. (20th September 2020) - Wenk, Benjamin M; Mbunkah, Herbert A; Nsanwe, Ndi N; Mbu, Eyongetah T; Besong, Lydia M; Sama, Bella A; Orock, Emmanuel; Leemann, Christine; Metzner, Karin J
Abstract: Objectives: In Cameroon, the integrase (IN) strand transfer inhibitor (INSTI) dolutegravir was recently introduced for the treatment of HIV-1 infection. Since pretreatment HIV-1 drug resistance can jeopardize the success of ART, and considering the high heterogeneity of circulating HIV-1 subtypes in Cameroon, we investigated the prevalence of pretreatment HIV-1 resistance to INSTIs. Methods: Fingerprick dried blood spot samples were collected from 339 newly diagnosed HIV-1-infected individuals between 2015 and 2016 in four hospitals in Cameroon. Universal primers were designed to amplify the HIV-1 IN region from amino acid 1 to 276. Amplicons were sequenced with Illumina next-generation sequencing and analysed with the Polymorphism Analysis Sequencing (PASeq) platform, using the Stanford HIV Drug Resistance Database to interpret HIV-1 drug resistance mutations (DRMs). Results: The amplification/sequencing success rate was 75.2% with 255/339 sequences obtained. Applying a cut-off of 1%, major DRMs to INSTIs were detected in 13 (5.1%) individuals, but only 1 individual harboured an INSTI DRM (E92G) at a nucleotide frequency ≥15%. However, 140/255 (54.9%) individuals harboured polymorphic accessory INSTI DRMs, mainly at high frequencies. In line with that observation, HIV-1 subtype diversity among individuals was high. Conclusions: Pretreatment HIV-1 resistance to INSTIs was low in the study sites, which supports the use of INSTIs in Cameroon. Nevertheless, further studies are necessary to assess the impact of polymorphic accessory INSTI DRMs on INSTI-based ART regimens.